2021
DOI: 10.4000/vertigo.29723
|View full text |Cite
|
Sign up to set email alerts
|

Une frontière virtuelle : l’exploitation des ressources minérales profondes dans le Pacifique

Abstract: Le projet d’exploiter les ressources minérales marines profondes, qui remonte aux années 1960, est revenu au premier plan dans les années 2000, dans un contexte de course aux matières premières et de croissance rapide des économies émergentes, en particulier celle de la Chine. La mine sous-marine constitue une nouvelle frontière économique et technologique pour les firmes minières et le capital transnational tandis que les pays et territoires du Pacifique insulaire s’efforcent d’anticiper cette rencontre en re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recent studies on socio-ecological controversies, across all disciplines, focus mainly on material, discursive, and institutional factors in the short term to explain social mobilisation against political-economic elites. The few papers looking at long-term structural mechanisms also focus on conflicts between civil society and elites (Rainbow 2006;Barbier and Nadaï, 2015;Deuffic and Banos, 2020;Laurent and Merlin, 2021;Le Meur and Muni Toke, 2021;Massé, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies on socio-ecological controversies, across all disciplines, focus mainly on material, discursive, and institutional factors in the short term to explain social mobilisation against political-economic elites. The few papers looking at long-term structural mechanisms also focus on conflicts between civil society and elites (Rainbow 2006;Barbier and Nadaï, 2015;Deuffic and Banos, 2020;Laurent and Merlin, 2021;Le Meur and Muni Toke, 2021;Massé, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The discovery of potential deep‐sea resources generated an extension of the Indigenous sovereign claim over high seas as land and sea form a continuum in terms of representation and appropriation, despite the French legal control on ‘its’ EEZ. The status quo founded in 1961 of a sort of limited sovereignty embedded in a broader, metropolitan sovereignty is thus challenged by the emergence of deep sea mining and a broader concern about marine governance (reflected in the ‘Declaration on the ocean’ issued by the Territorial Assembly in 2019) in the conversation between Wallis and Futuna and, on the other hand, France (Le Meur and Muni Toke 2021).…”
Section: Orienting Sovereigntiesmentioning
confidence: 99%
“…French Pacific territories' responses to this ‘scramble for the Pacific’ (Fache et al 2021) are diverse, as shown by Marlène Dégremont in her contribution. Deep sea mining is viewed as a potential economic alternative in French Polynesia (Le Meur et al 2018) whereas it crystallizes growing tensions between customary and political authorities and the French state in Wallis and Futuna and it seems to be ‘ignored’ by the Coral Sea Natural Park in New Caledonia (Le Meur and Muni Toke 2021). The interplay between French sovereignty, Polynesian claims and environmental NGOs strategies results in changing configurations polarized by a tension between large‐scale Marine Protected Areas (MPAs) as new enclosures or forms of blue grabbing (Bennett and Govan 2015; Cornier and Leblic 2016) and large‐scale Marine Managed Areas (MMA) as exemplified in French Polynesia.…”
Section: Postcolonial Turnsmentioning
confidence: 99%